Penerapan Metode Decision Tree Dalam Menentukan Kelulusan Mahasiswa - Rahmadayanti, Fitria; Anggraini, Inda (Forum Kerjasama Pendidikan Tinggi, 2021)
The purpose of this study is to produce a prediction system for determining the determination of student graduation on time with the Decision Tree method at Pagaralam High School of Technology. If many students graduate not on time or exceed the specified limit will result in the accumulation of students in large numbers due to the imbalance of the number of students entering and exiting each graduation period so that it can cause the academic process does not run optimally. Decision Tree is a classification algorithm that can predict large amounts of data. The development method used is the Rapid Application Develoment (RAD) method consisting of Requirement Planning (Requirements Planning), Workshop Design, Implementation (Implementation). This research can help the Pagaralam High School of Technology in seeing whether students will graduate on time or not